Influence of water quality on satellite laser altimeter underwater measurement accuracy - Lu, Qingkai; Wu, Jianjun; Ma, Chen; Xia, Haobin; Zhang, Siqin; Xu, Haojun; Gan, Feng; Zhao, Zimeng (Frontiers in Environmental Science, 2025)
With the growing demand for global water environment monitoring, satellite laser altimeters (SLA) have considerable advantages for underwater measurements. However, changes in suspended solids, turbidity, and other optical properties of water affect the propagation of SLA laser pulses in water. This can affect the accuracy and reliability of the measurements. This study analyzed the impact of water quality changes in the Oahu Island region of Hawaii on the accuracy of SLA un-derwater measurements based on ICESat-2, MODIS, Landsat-8, and in situ data. Underwater photons were obtained from ICESat-2 ATL03 data through an Adaptive Elevation Difference Threshold, combined with in situ data to calculate the potential altimetry deviation. Using the water quality data inverted from Landsat-8 as a reference, MODIS kd490 was implemented through random forest regression. The impact of water quality changes on the SLA accuracy was quantified by combining the altimetry bias and water quality data that matched the laser footprint. There is a positive correlation between water quality and photon water permeability. The more turbid the water quality, the smaller the proportion of photons that can penetrate the water surface. The maximum measurement deviation caused by multiple scattering of the water body could reach the meter level. Future underwater bathymetry corrections need to consider the impact of multiple scattering. The findings are of considerable importance for environmental protection, resource management, policy formulation, and SLA data processing.